RESPONS OF BREAD WHEAT YIELD AND IT,S COMPONENTS TO BORON AND VITAMIN C FOLIAR APPLIED - & Zeboon, Al-Hilfy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
Field experiment was conducted during 2010 – 2011 and 2011 – 2012 winter seasons at the Experimental Farm, Department of Field Crops, College of Agriculture University of Baghdad. RCBD design with four replications were used to study the effect of Boron and vitamin C foliar applied on yield and some it,s components of bread  wheat Triticum aestivum L. cv. Abu – Ghraib-3. The experiment involved two factors ,the first was boron foliar in five concentrations  0,100, 200, 300, 400 mg L-1  the second was vitamin C foliar applied in five concentrations 0,1,2,3,4, gmL-1 at booting stage. Results of the experiment showed :300 mg B L-1 was  superior in grain yield 6.726,6.771 Mg ha-1)   for both seasons and some yield components ( spike number for the second season 574.9 spike m-2 , fertility 97.27% 97.34% and number of grain 66.39 , 65,22 grain spik-1 ) for both seasons . Foliar of Vitamin C with 4 gm L-1 was significantly affected grain yield (6.820 , 6.879 Mg ha-1 ) for both seasons respectively . Foliar of Vitamin C with 4 gm L-1 was significantly affected on grain yield and some it,s components (6.820 , 6.878 Mg ha-1 ) as compared to control which gave (4.882 ,4.906 Mg ha-1) for both seasons, respectively .The interaction between two factors was significant in some characters ( number of spike and grain yield ).